Kreativitas Siswa dan Upaya Guru Bimbingan dan Konseling/Konselor dalam Pengembangannya - Arrahmil Hasanah; Asmidir Ilyas; Afdal Afdal (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2018)
Creativity is a person's ability to create something new. Creativity of students need to be cultivated by all of their environment, such as their parents, teacher’s subjects, or guidance and counseling teacher. This research aims to describe the creativity of the students in SMPN 2 Padang, and describe the efforts to be made by the teacher guidance and counseling in developing the creativity of students. The type of this research is the research of combinations (Mixed method), the populations of this research are 536 people, with 88 samples using proportional random sampling technique. The source of this data research is from primary data collected by using paper test to appereance the creativity (AUKREF) and interviews with the guidance and counseling teachers. The results of this research are: (1) The creativity level of the students are in good category (71.6%) with the average score of student is 54.34. (2) The efforts made by guidance and counseling in developing students' creativity is to create a sense of safe to the students, recognizing the advantages of students creative, strategies or tips in favor of the students to be more creative, to help student who has the creativity to understanding their differences with the other children, give opportunities for creative students to communicate ideas, and provide guidance and counseling services in developing students' creativity. Based on these findings, it hopefully the guidance and counseling teacher can optimize guidance and counseling services in developing students' creativity at SMPN 2 Padang.